الاستفادة من الأجنة المجهضة والزائدة عن الحاجة في التجارب العلمية وزراعة الأعضاء: دراسة فقهية مقارنة - سوفي, نور الإيمان (University of Eloued جامعة الوادي, 2019)
This research treats an imoprtant medical modern subject which is « the wisdom of the benefit of the aborted and excess embryos in the scientific experiments and the organs transplants .However , it deals with the legal controls and judgments of this matter by giving the modern jurists’ points of views and their diligences In addition , this researsh deals with the matters touching this subject in order to give a clear Islamic view about these updates. Finally , this reseach is ended by imprtant results and recommmendates. Basides chosing the say that accepts the benefit of these embryos that takes into consideration certain and specific conditions .
كتاب. إصدارات مخبر الدراسات الفقهية والقضائية. جامعة الوادي
Keywords: الأجنة المجهضة، الأجنة الزائدة، التجارب العلمية، زراعة الأعضاء، دراسة فقهية